An Examination of Tourism Transport Safety Aspects at Sd Muhammadiyah Sidoarum, Sleman Regency - Ardiansyah, Burhan Dwi (Journal of Public Transportation Community, 2024)
This research was conducted to analyze the condition of vehicles and permits in an effort to improve the safety of tourism transportation at SD Muhammadiyah Sidoarum, Sleman Regency. The research methods used included direct observation, interviews, and document studies. The collected data was analyzed using a qualitative approach and descriptive analysis techniques. The results of the research show that tourism transport vehicles and vehicle permits are in good condition. The study also indicates that the examination of document completeness, vehicle technical conditions, equipment, and cleanliness are crucial in creating a safe, comfortable, and satisfying environment for passengers. Safety improvement has a positive impact on the reputation of travel organizers and has the potential to increase participation and support for tourism activities in the future. This research provides a better understanding of the importance of inspecting tourist vehicles and its influence on enhancing safety in school tourism trips.